A Comparative Study between Pseudo-static and Dynamic Analyses on Rock Wedge Stability of an Arch Dam - Hasan Mostafaei; Morteza Sohrabi Gilani; Mohsen Ghaemian (Salehan Institute of Higher Education, 2018)
In this study, the abutment stability of arch dams for two cases of pseudo-static and dynamic methods were compared based on limit state equilibrium method. For the pseudo-static approach, unit accelerations were applied to the model in three directions for calculating thrust forces. For dynamic analysis, three components of ground acceleration time histories of Kobe earthquake, 1979 were applied to the finite element model of dam-foundation-reservoir, and the thrust forces were obtained. The effect of reduction factors in pseudo-static analysis is investigated in order to obtain the reduction factor that corresponds to wedge movement in dynamic analysis. For this purpose, the reduction factors have been increased from 0.5 to 1. The obtained results indicate that pseudo-static results are more conservative than the dynamic analysis method for small reduction factors and the reduction factor plays a key role on the abutment stability analysis.